2021
DOI: 10.3389/frwa.2021.633046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Inequalities in Flood Exposure: A Matter of Scale

Abstract: Studies on inequalities in exposure to flood risk have explored whether population of a lower socio-economic status are more exposed to flood hazard. While evidence exist for coastal flooding, little is known on inequalities for riverine floods. This paper addresses two issues: (1) is the weakest population, in socio-economic terms, more exposed to flood hazard, considering different levels of exposure to hazard? (2) Is the exposure to flood risk homogeneous across the territory, considering different scales o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This results in the inability to determine the frequency of exposure for agricultural land, which could be addressed through national-scale mapping initiatives. Internationally, there is evidence that the level of exposure and vulnerability of populations can be altered dependent on the scale at which analyses are conducted, demonstrating the importance of consistency in modeling [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…This results in the inability to determine the frequency of exposure for agricultural land, which could be addressed through national-scale mapping initiatives. Internationally, there is evidence that the level of exposure and vulnerability of populations can be altered dependent on the scale at which analyses are conducted, demonstrating the importance of consistency in modeling [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the source data were disaggregated proportional to the ancillary data without performing the IDM and areal interpolation. Some examples of other studies with similar approaches are Fielding and Burningham (2005) and Poussard et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Rasch (2017) discussed income inequality as a predictor for vulnerability to floods at a municipal level in Brazil. On a household scale, low‐income groups are overall more exposed to river floods (Erman et al, 2018; Fielding & Burningham, 2005; Osberghaus, 2021; Poussard et al, 2021). In addition, Henry et al (2017) found that the location of the low‐income households is more prone to flooding in the Bangkok area.…”
Section: Introductionmentioning
confidence: 99%
“…Disaster shocks exacerbate poverty, according to research by (Carter et al, 2007;Rodriguez-Oreggia et al, 2013). More people in low-income households are at risk from river floods (Erman et al, 2018;Osberghaus, 2021;Poussard et al, 2021). Natural disasters, such as floods, have the potential to exacerbate class divisions by reducing economic output.…”
Section: The Impacts Of Floods Disasters On the Poverty And Income Di...mentioning
confidence: 99%